Sports heroes and mass sports participation: The (double) paradox of the 'German tennis boom' - Arne Feddersen; Sven Jacobsen; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2009)
The major sporting success of one's countrymen and women is often supposed to promote the growth of general participation in that sport. This study is the first to analyse the impact of sports heroes on the membership figures of the corresponding sports association by means of an econometric analysis. We do so by evaluating the so-called 'Boris Becker effect' by simultaneously testing for the effects of the rise and retirement of the three stars Boris Becker, Stefanie Graf, and Michael Stich. As a first paradox, our results indicate a negative tennis growth effect associated with the time period of the ascendency of the sport stars. With the first paradox, their retirement should then have a positive effect. In this sense, our second result of a statistically negative tennis growth since the declining success of the German tennis stars must be regarded as a second paradox.
Keywords: L83; C23; 330; Tennis; Sport Association Memberships; Boris Becker Effect; Mass Sport Participation